Iconic Words Denoting Food Consumption (on the Material of the Russian Language) - N. N. Noland; E. I. Besedina (Дискурс)
Introduction. The article presents the findings of a study on establishing the sound symbolic status of individual phonemes and phonesthemes in the designations of “noisy and greedy consumption of food and drinks”, carried out on the material of the Russian dialect language at the junction of iconicity and dialectology and is a continuation of the joint work of the authors on the research of the sound symbolic role of certain phonemes in designation of the concepts of “biting, gnawing”, “chomping, smacking” and “sucking in” in the three corresponding lexical-semantic groups of the English dialect lexemes.Methodology and sources. The material for this work is the corpus of lexemes denoting swallowing, obtained by continuous sampling from the Dictionary of Russian Folk Dialects, ed. by F.P. Filin. The research was carried out using phonosemantic analysis.Results and discussion. The study clearly demonstrated that the lexicon of the Russian dialects, similar to the dialect vocabulary of the English language, contains quite an impressive number of iconic words and contains sets of lexemes that, having similar or virtually identical semantics, differ from each other by only one or two phonemes. The analysis of the corpus of the material allowed the authors to conclude that in cases with iconic vocabulary we do not actually deal with two (or more) different words, but with the same word, that can be described in terms of sound symbolic hyperlexems.Conclusion. The dialect lexicon of the Russian language, like the dialect lexicon of the English language, possessing such a distinctive feature as expressiveness, gives us a particularly rich and interesting sound-symbolic material that can be studied within the framework of dialect phonosemantics since it contains numerous and diverse groups of sound-symbolic words and can contribute to the theory of iconicity.